Patterns and drivers of beta diversity across geographic scales and lineages in the Macaronesian flora - Mouton, Lea (2023)
Aim How spatial, historical and ecological processes drive diversity patterns remains one of the main foci of island biogeography. We determined how beta diversity varies across spatial scales and among organisms, disentangled the drivers of this variation, and examined how, consequently, biogeographic affinities within and among archipelagos vary among land plants. Location Macaronesia. Taxon Bryophytes, pteridophytes, spermatophytes. Methods Species turnover and nestedness were compared within and among archipelagos across taxonomic groups. The relationship between species turnover and nestedness, climatic, geological and geographic factors was analysed using generalized dissimilarity models. Results Species turnover, but not nestedness, increased with the geographic scale. This increment decreased from spermatophytes, pteridophytes and bryophytes, wherein the median turnover was less than half that in spermatophytes. Bryophytes exhibited a significantly higher nestedness and lower turnover than spermatophytes. Extant climatic conditions and island age contributed the most to all models but the importance of island age for bryophyte and pteridophyte turnover was marginal. Spermatophyte floras clustered by archipelago, whereas the clustering patterns in pteridophyte and bryophyte floras reflected macroclimatic conditions. Main Conclusions The lower increment of species turnover with spatial scale and the higher nestedness in bryophytes and pteridophytes than in spermatophytes reflect the variation in dispersal capacities and distribution ranges among land plants. Accordingly, extant climatic conditions contributed more to explain turnover in bryophytes and pteridophytes than in spermatophytes, whereas factors associated with dispersal limitations, including island age, geographic distance and archipelago structure, exhibited the reverse trend. The differences in beta diversity patterns, caused by different responses of Macaronesian land plant lineages to the main factors shaping their community composition, explain their different biogeographic affinities. These differences reflect a distinct origin and different mechanisms of speciation among Macaronesian land plant lineages and archipelagos.